Energetic utilisation of refuse derived fuels from landfill mining. (April 2017) - Rotheut, Martin; Quicker, Peter
Highlights: Untreated material and RDF, gained from a landfill, were utilised in an industrial WtE-plant. Incineration of untreated materiel was only successful in high dilution with normal waste. RDF can be mono-incinerated, a 1:1 mixing with normal waste seems to be reasonable. Emissions are affected, but can be handled with conventional flue gas treatment. Abstract: The residence of municipal solid waste within a landfill body results in a significant change of material properties. Experiences with the energetic utilisation of the burnable fractions from formerly landfilled waste are hardly documented, the influence of refuse derived fuels (RDF) from such materials on the performance of modern waste-to-energy plants is not sufficiently described in scientific literature. Therefore this study focuses on the energetic utilisation of refuse derived fuel from landfilled waste, processed in a mechanical waste treatment facility, and the impact of the material on the operation of the incineration plant. Additionally, the possibility of direct combustion of non-pre-treated excavated landfill material has been evaluated in the same facility. First, sampling and analysis of the fuel has been carried out. Based on this, a large-scale combustion experiment was planned and conducted in an industrial waste-to-energy plant. Steam mass flow rate, concentration of harmful substances in the raw gas, as well as total emissions of the facility have been monitored in detail. Furthermore, the influence of the landfilled material on the additive consumption has been determined. The combustion residues (bottom ash) were also sampled and analysed. Based on the evaluation of operating data and analysis of both fuel and residue, suitable thermal treatment approaches for the refuse-derived fuel and the non-pre-treated excavated material have been assessed.